Suppressive effects of deep balanced anesthesia on cellular immunity and protein expression: a randomized-controlled pilot study - Nguyen, Xuan-Duc; Horn, Audrey; Fischer, Dania; Beck, Grietje; Spannenberger, Cora C.; Gaudilliere, Brice; Horn, Jean-Louis; Thierse, Hermann-Josef; Frietsch, Thomas (BMC anesthesiology, 2025)
It is questionable whether or not a short period of deep anesthesia can have long lasting effects on immune suppression.
Gesehen am 07.08.2025